Discursive Сonstruction of the Сoncept of «reform» in the Political Field (on the example of Transcripts of the Verkhovna Rada of Ukraine) - Borysenko, Olena (Ukrainian Sociological Journal, 2020)
The article explores official political discourse of Ukraine and its interpretation on the subject of constructing the concept of “reform”. The main methods of sociological information obtaining and analyzing were preliminary content analysis of the selected sources and discourse analysis of the collected information. The theoretical and practical significance of the work located in adaptation of the cognitive theory of discourse and critical discourse analysis to sociological research and also conceptualization the category of discursive construct. During the analysis, forms of constructing of reform concept within the framework of political discourse have been developed. The official, constructive and oppositional forms of construction were highlighted, a number of illustrations from the meetings of the VRU are applied. On the basis of this, a symbolic struggle is described around the concept of “reform”, in which discursive elements of the construction of reality became the main tool for winning an audience. The most common informational occasions and implications on the part of the official (European integration and democratization) and the opposition forms of construction (social inequality, pauperization of the population and the incorrect implementation of reforms by political competitors) are identified. It is emphasized that the contexts and meanings of the symbolic struggle is aimed at the electorate, and not at political competitors, therefore society as an object of discourse is interpreted as a victim of symbolic violence, and the concept of reform is interpreted as an instrument of this process. We established within the framework of research: the general declarative nature of Ukraine’s political discourse about the category of reform, as well as the formation of this discursive unit as a subject of symbolic struggle within the framework of opposition-coalition conflicts through the exploitation of the doxa format in all studied fields; the background process of loss of universal sense by the category of «reform» through its excessive exploitation within the framework of political discourse in order to achieve the favor of society. Methodological limitations and heuristic perspectives are described also.